Nutritional and Functional Properties of Some Promising Legumes Protein Isolates - Butt, Masood Sadiq; Batool, Rizwana (Pakistan Journal of Nutrition, 2010)
Proteins are essential component of diet performing multifarious role in human body. Present project was an attempt to extract and characterize legumes protein isolates for their functional properties. Four different legumes i.e. cowpea, pigeon pea, peas and mungbean were evaluated for protein content, functional properties and their ability to improve nutritional quality of foods. Cowpea exhibited maximum protein content 27.88±1.95% followed by mungbean, peas and pigeon pea. As for as functional properties are concerned, cowpea protein isolates showed highest bulk density 0.71±0.05 g/cm3 however, maximum protein solubility 82±4.97 was observed in pea protein isolates. Maximum water and oil absorption capacity 163±10.05, 168±11.72% was observed in mungbean and pigeon pea protein isolates, respectively. Likewise different legumes protein isolates showed significant results for emulsifying, foaming and gelling properties.